Immediate impact of stay-at-home orders to control COVID-19 transmission on socioeconomic conditions, food insecurity, mental health, and intimate partner violence in Bangladeshi women and their families: an interrupted time series - Hamadani, Jena Derakhshani; Hasan, Mohammed Imrul; Baldi, Andrew J; Hossain, Sheikh Jamal; Shiraji, Shamima; Bhuiyan, Mohammad Saiful Alam; Mehrin, Syeda Fardina; Fisher, Jane; Tofail, Fahmida; Tipu, S M Mulk Uddin; Grantham-McGregor, Sally; Biggs, Beverley-Ann; et al. (The Lancet global health, 2020)
Stay-at-home orders (lockdowns) have been deployed globally to control COVID-19 transmission, and might impair economic conditions and mental health, and exacerbate risk of food insecurity and intimate partner violence. The effect of lockdowns in low-income and middle-income countries must be understood to ensure safe deployment of these interventions in less affluent settings. We aimed to determine the immediate impact of COVID-19 lockdown orders on women and their families in rural Bangladesh. An interrupted time series was used to compare data collected from families in Rupganj upazila, rural Bangladesh (randomly selected from participants in a randomised controlled trial), on income, food security, and mental health a median of 1 year and 2 years before the COVID-19 pandemic to data collected during the lockdown. We also assessed women's experiences of intimate partner violence during the pandemic. Between May 19 and June 18, 2020, we randomly selected and invited the mothers of 3016 children to participate in the study, 2424 of whom provided consent. 2414 (99·9%, 95% CI 99·6–99·9) of 2417 mothers were aware of, and adhering to, the stay-at-home advice. 2321 (96·0%, 95·2–96·7) of 2417 mothers reported a reduction in paid work for the family. Median monthly family income fell from US$212 at baseline to $59 during lockdown, and the proportion of families earning less than $1·90 per day rose from five (0·2%, 0·0–0·5) of 2422 to 992 (47·3%, 45·2–49·5) of 2096 (p<0·0001 comparing baseline with lockdown period). Before the pandemic, 136 (5·6%, 4·7–6·6) of 2420 and 65 (2·7%, 2·1–3·4) of 2420 families experienced moderate and severe food insecurity, respectively. This increased to 881 (36·5%, 34·5–38·4) of 2417 and 371 (15·3%, 13·9–16·8) of 2417 during the lockdown; the number of families experiencing any level of food insecurity increased by 51·7% (48·1–55·4; p<0·0001). Mothers' depression and anxiety symptoms increased during the lockdown. Among women experiencing emotional or moderate physical violence, over half reported it had increased since the lockdown. COVID-19 lockdowns present significant economic, psychosocial, and physical risks to the wellbeing of women and their families across economic strata in rural Bangladesh. Beyond supporting only the most socioeconomically deprived, support is needed for all affected families. National Health and Medical Research Council, Australia.